2008 IEEE International Symposium on Information Theory 2008
DOI: 10.1109/isit.2008.4595095
|View full text |Cite
|
Sign up to set email alerts
|

LDPC codes from voltage graphs

Abstract: Abstract-Several well-known structure-based constructions of LDPC codes, for example codes based on permutation and circulant matrices and in particular, quasi-cyclic LDPC codes, can be interpreted via algebraic voltage assignments. We explain this connection and show how this idea from topological graph theory can be used to give simple proofs of many known properties of these codes. In addition, the notion of abelianinevitable cycle is introduced and the subgraphs giving rise to these cycles are classified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…A similar observation for the theta-graph case is shown in [15]. Moreover, in [5] it is also shown that any such "inevitable cycle" in a derived graph specified by an abelian voltage assignment results from a base graph containing one of these two types of subgraphs. This provides a full classification for the cycles that will always occur in the derived graph when abelian voltages are used (regardless of how they are assigned), due to the base graph structure.…”
Section: A Abelian Voltagessupporting
confidence: 74%
See 3 more Smart Citations
“…A similar observation for the theta-graph case is shown in [15]. Moreover, in [5] it is also shown that any such "inevitable cycle" in a derived graph specified by an abelian voltage assignment results from a base graph containing one of these two types of subgraphs. This provides a full classification for the cycles that will always occur in the derived graph when abelian voltages are used (regardless of how they are assigned), due to the base graph structure.…”
Section: A Abelian Voltagessupporting
confidence: 74%
“…This suggests that noncommuting voltage assignments have a greater potential in yielding derived graphs with large girth. The result on inevitable cycles in [5] provides an alternative short proof that the girth is always at most 12 for codes constructed using commuting permutation matrices in arrays that contain a sub-array of 2 × 3 nonzero permutation matrices. This limitation of girth 12 was originally shown in [7] and later by various groups (see for example, [17]).…”
Section: A Abelian Voltagesmentioning
confidence: 98%
See 2 more Smart Citations
“…The terminology "base graph" originates from graph theory and is used, for example, in [11]. It differs from the terminology used in [6], [9], where protograph or seed graph are used.…”
Section: Base Matrices Voltages and Their Graphsmentioning
confidence: 99%